2015
DOI: 10.1371/journal.pone.0145208
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Fairness and Efficiency: The Impact of Identity-Blind and Identity-Conscious Accountability on Applicant Screening

Abstract: This study compared two forms of accountability that can be used to promote diversity and fairness in personnel selections: identity-conscious accountability (holding decision makers accountable for which groups are selected) versus identity-blind accountability (holding decision makers accountable for making fair selections). In a simulated application screening process, undergraduate participants (majority female) sorted applicants under conditions of identity-conscious accountability, identity-blind account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Indeed, research has shown that when decision makers are held accountable for making fair selections, qualifications of candidates play a more vital role and their biases tend to reduce. 46,47 The study's findings are in line with our expectations and earlier research, except for the finding that average bachelor grade was partly able to explain the relationship between students' ethnicity and receiving an upgrade. However, our data showed that average bachelor grade itself was also influenced by students' ethnicity.…”
Section: Rq1: Ethnicity-related Differences In Grades In Broadly Sampsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, research has shown that when decision makers are held accountable for making fair selections, qualifications of candidates play a more vital role and their biases tend to reduce. 46,47 The study's findings are in line with our expectations and earlier research, except for the finding that average bachelor grade was partly able to explain the relationship between students' ethnicity and receiving an upgrade. However, our data showed that average bachelor grade itself was also influenced by students' ethnicity.…”
Section: Rq1: Ethnicity-related Differences In Grades In Broadly Sampsupporting
confidence: 90%
“…Also, when assessors are held accountable, by asking them to legitimate their evaluation decisions, grade differences as a result of ethnicity (and other irrelevant information) can be reduced. Indeed, research has shown that when decision makers are held accountable for making fair selections, qualifications of candidates play a more vital role and their biases tend to reduce …”
Section: Discussionmentioning
confidence: 99%
“…Third, scenario-based studies can also be criticized on the ground of their lower external validity, but serve other purposes than field studies (like correspondence audit tests) as they may be conducted in a more controlled way and may test contingencies surrounding discriminatory decisions in hiring. Future studies, however, could investigate more and other moderators related to the applicant (like gender; Sidanius and Veniegas, 2000 ), the job (like type of job, differences in responsibility, and decision-making power; Abrams et al, 2016 ), and the recruiter (like prejudices and other individual difference variables of relevance; see Self et al, 2015 ; Fasbender and Wang, 2017 ). For instance, Brtek and Motowidlo (2002) and Self et al (2015) showed that recruiters’ accountability might affect discriminatory decision-making, with some types of accountability (like identity-blind accountability) leading to less bias and more objective decision-making than other types of accountability (like identity-conscious accountability).…”
Section: Discussionmentioning
confidence: 99%
“…One alternative, therefore, could be the use of demographically diverse panels of interviewers instead of one-to-one interviews (which may reduce bias but may be less practical to organize). Holding interviewers accountable for their selection decisions may be another interesting strategy to explore (e.g., Self et al, 2015 ). Finally, study findings may also be valuable to coach and educate ethnic minority job seekers about potential misinterpretations when (not) using certain IM-tactics as some tactics might be considered more (or less) appropriate than others ( Spong and Kamau, 2012 ).…”
Section: Discussionmentioning
confidence: 99%